2012
DOI: 10.2478/v10102-012-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic levels in tube-wells water, food, residents' urine and the prevalence of skin lesions in Yatenga province, Burkina Faso

Abstract: The aim of the present study was to evaluate the levels of arsenic in tube-well water, food and residents’ urines samples in Yatenga province, Burkina Faso. The prevalence of skin lesions was evaluated as well. The study was cross-sectional in design. It was conducted during April 2009. Permanent residents of 20 villages were included in the study. Water samples were collected from 31 tube-wells located in the selected villages. Tomatoes, cabbages, and potatoes produced in the selected village were randomly sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Moreover, in affected countries, high-As concentrations were found only in some areas. For example, in Burkina Faso, high-As concentrations were found only in the northern region (Smedley et al 2007;Somé et al 2012;Nzihou et al 2013). In Botswana and Ethiopia, only the Okavango Delta and Rift Valley, respectively, seem be concerned with arsenic pollution (Reimann et al 2003;Huntsman-Mapila et al 2006;Rango et al 2010;Dsikowitzky et al 2013;Mladenov et al 2013;Rango et al 2013).…”
Section: Probable Extent Of As Contamination In Africamentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, in affected countries, high-As concentrations were found only in some areas. For example, in Burkina Faso, high-As concentrations were found only in the northern region (Smedley et al 2007;Somé et al 2012;Nzihou et al 2013). In Botswana and Ethiopia, only the Okavango Delta and Rift Valley, respectively, seem be concerned with arsenic pollution (Reimann et al 2003;Huntsman-Mapila et al 2006;Rango et al 2010;Dsikowitzky et al 2013;Mladenov et al 2013;Rango et al 2013).…”
Section: Probable Extent Of As Contamination In Africamentioning
confidence: 94%
“…Recent reports have suggested that two deaths linked to high-As drinking water have occurred in this area (Ouedraogo 2006). Besides, Somé et al (2012) identified that 29.26 and 46.34 % of the population (240 persons) in 20 villages in Yatenga province, Burkina Faso, were affected by melanosis and keratosis, respectively. According to them, this public health problem in Yatenga linked to arsenic is due to drinking water.…”
Section: Health Hazard Linked To High-as Water In Africamentioning
confidence: 98%
“…Groundwater contamination by arsenic levels is up to 1630 μg·L −1 due to mining activities having been measured [3]. The analysis and epidemiological study reported in reference [4] has established a high correlation between the presence of Arsenic in patients' urines and the concentration of Arsenic in their source of drinking water in Yatenga, one of the four provinces of the North region. Solution to this problem was supposed to drill 100 new bore-hole in order to replace access point above national standards.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies in the northern part of Burkina Faso showed that more than 50 % of borehole water had arsenic content higher than WHO recommended values (10 ppb). Sanitary damages have also been pointed out including keratosis cases 2. Health implications resulting in consumption of arsenic contaminated water are dermatologic modifications (hyperpigmentation, keratosis) for short term and skin cancer and internal malignancies for long term exposition 3.…”
Section: Introductionmentioning
confidence: 99%